THE EFFECT OF PRICE AND SERVICE QUALITY ON LOYALTY THROUGH CUSTOMER SATISFACTION OF FASHION PRODUCTS ON TOKOPEDIA - Yulisetiarini, Diah; Amalianingtias, Dwi; Subagio, Ari (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research is an explanatory study aimed at examining and discussing the influence of price and service quality on loyalty through customer satisfaction of fashion products on Tokopedia. This study uses non-probability sampling with purposive sampling method. The sample size used in the study was 230 respondents. The source of data used in this study is primary data obtained by distributing online questionnaires to respondents who are consumers of fashion products on Tokopedia. The data analysis method uses path analysis with the Statistical Program for Social Science (SPSS). The results showed that price significantly affects satisfaction. Service quality significantly affects customer satisfaction. Customer satisfaction significantly affects customer loyalty. Price significantly affects loyalty. Service quality significantly affects loyalty. Price significantly affects loyalty through customer satisfaction. Service quality significantly affects loyalty through customer satisfaction.